Factors Affecting the Acceptance of Live Streaming Technology for Purchasing Products by Ubon Ratchathani Rajabhat University Students: Case Study of TikTok Application - Kitpermkiad, Santanee; Srisawatsakul, Charnsak (Journal of Applied Informatics and Technology, 2025)
Recently, live streaming technology has become increasingly popular worldwide due to its ability to enable viewers to interact and become closer to influencers in the online world. In Thailand, the platform that is highly popular for live streaming is TikTok, which started as an application for sharing short videos. It features a live streaming option called TikTok LIVE, which has become increasingly popular, especially among Generation Z. Importantly, this live streaming channel has also transformed into a venue for selling products and services. Therefore, this research aims to identify the factors affecting the intention of purchasing products through live streaming on TikTok among Generation Z in Ubon Ratchathani Province. The population for this study was the students of Ubon Ratchathani Rajabhat University. The data consisted of 239 sample participants. The data were collected using an online questionnaire, which was verified by three experts. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the hypothesis and explore the relationships between variables. The study found that service quality, system quality, perceived ease of use, and information quality significantly influenced the purchase intentions of Ubon Ratchathani Rajabhat University students through the TikTok application.